2019
DOI: 10.1101/695155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nestin selectively facilitates the phosphorylation of the Lissencephaly-linked protein doublecortin (DCX) by cdk5/p35 to regulate growth cone morphology and Sema3a sensitivity in developing neurons

Abstract: AbstractNestin, an intermediate filament protein widely used as a marker of neural progenitors, was recently found to be expressed transiently in developing cortical neurons in culture and in developing mouse cortex. In young cortical cultures, nestin regulates axonal growth cone morphology. In addition, nestin, which is known to bind the neuronal cdk5/p35 kinase, affects responses to axon guidance cues upstream of cdk5, specifically, to Sema3a. Changes in growth cone morpholog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…DCX/Dcx is a modulator of neuronal growth cone morphology and the underlying MT and F-actin organisation (Bielas et al, 2007; Bott et al, 2020; Fu et al, 2013; Jean et al, 2012) and nucleates and stabilises 13-protofilament MTs in vitro (Moores et al, 2004). We therefore undertook cryo-ET of hippocampal neuron growth cones from Dcx knockout (KO) mice and analysed the detailed ultrastructural data, with a focus on the cytoskeleton (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DCX/Dcx is a modulator of neuronal growth cone morphology and the underlying MT and F-actin organisation (Bielas et al, 2007; Bott et al, 2020; Fu et al, 2013; Jean et al, 2012) and nucleates and stabilises 13-protofilament MTs in vitro (Moores et al, 2004). We therefore undertook cryo-ET of hippocampal neuron growth cones from Dcx knockout (KO) mice and analysed the detailed ultrastructural data, with a focus on the cytoskeleton (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since neural cell adhesion molecule 2 (NCAM2) and neuronal regeneration related protein (NREP, also known as P311) are known to be involved in neuronal migration and neurite outgrowth (Fujitani et al, 2004;Parcerisas et al, 2021), these results suggest that AA suppressed the neurite outgrowth of immature granule cells via the downregulation of Ncam2 and Nrep. The decrease in the transcript level of Nes might also be related to the impairment of neurite outgrowth of the DCX + cells since it has been reported that nestin forms a complex with DCX to regulate the growth cone morphology in developing cortical neurons (Bott et al, 2020). In our previous study, exposure to glycidol, a neurotoxicant causing distal axonopathy similar to that induced by AA, also resulted in gait abnormality and a decrease in the densities of type-3 NPCs and immature granule cells and suppressed the gene expressions of Ncam2, suggesting that AA share a similar target mechanism with glycidol for disruption of hippocampal neurogenesis (Akane et al, 2013(Akane et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of DCX to tubulin increases MT homeostasis in neurons, which can be disturbed via knockout of the DCX gene sequence using an inducible transgenic mouse approach [40]. Additionally, DCX is expressed in various regions of the developing nervous system and is regarded as a gold standard biomarker for identifying neuronal precursors and migration during adult neurogenesis [41,42].…”
Section: Types Of Mt Regulatory Proteinsmentioning
confidence: 99%